Integrated Process of Coal Fast Pyrolysis in a Fluidized Bed Reactor With Reforming Reaction of Simulated Fuel Gas to Promote Light Tar Evolution - Li, Chao; Luo, Zhongyang; Fang, Mengxiang; Yan, Qike; Cen, Jianmeng (Frontiers in Energy Research, 2021)
The evolution behavior of the light tar during coal fast pyrolysis under inert gas, simulated fuel gas (SFG) atmosphere, and catalytic reformation of simulated (CRS) fuel gas over Ni/Al2O3 was studied in this article. The light tar was recovered from the distillation of the crude tar at the temperature of 300°C and subsequently subjected to detection through the GC-MS analysis. It was found that both SFG and CRS over Ni/Al2O3 significantly enhanced the light tar yield, but a little effect was shown on the heavy tar yield. According to the molecular structure characteristics, the compounds in the light tar could be classified into several groups: aromatic components, phenol components, aliphatic components, heteroatom components, and O-containing components (phenol compounds excluded). It was demonstrated that the selectivity of each component in the light tar varied significantly with the pyrolysis atmosphere and temperature. The evolution of the aromatic components took the dominant role in the light tar produced at high temperature. The SFG and CRS contributed markedly to enhancing the evolution of the O-aromatic components in the light tar, whereas they suppressed the evolution of the O-aliphatic components and the phenol components in the light tar at high temperature.